ISSUES OF USING ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN POLITICAL PROCESSES - Suyunov Behzod Bakhodirovich (Journal of Artificial Intelligence and Digital Economy, 2024)
This article analyzes the importance of using artificial intelligence in political processes, as well as its impact on politics. It was also noted that it is necessary to establish the specifics of artificial intelligence technologies, as well as the possible limits of its application in political processes. In addition, priority areas for the use of artificial intelligence technologies in political processes were identified.